A therapeutic antibody targeting osteoprotegerin attenuates severe experimental pulmonary arterial hypertension - Arnold, Nadine D.; Pickworth, Josephine A.; West, Laura E.; Dawson, Sarah; Carvalho, Joana A.; Casbolt, Helen; Braithwaite, Adam T.; Iremonger, James; Renshall, Lewis; Germaschewski, Volker; McCourt, Matthew; Bland-Ward, Philip; et al. (Nature communications, 2019)
Pulmonary arterial hypertension (PAH) is a rare but fatal disease. Current treatments increase life expectancy but have limited impact on the progressive pulmonary vascular remodelling that drives PAH. Osteoprotegerin (OPG) is increased within serum and lesions of patients with idiopathic PAH and is a mitogen and migratory stimulus for pulmonary artery smooth muscle cells (PASMCs). Here, we report that the pro-proliferative and migratory phenotype in PASMCs stimulated with OPG is mediated via the Fas receptor and that treatment with a human antibody targeting OPG can attenuate pulmonary vascular remodelling associated with PAH in multiple rodent models of early and late treatment. We also demonstrate that the therapeutic efficacy of the anti-OPG antibody approach in the presence of standard of care vasodilator therapy is mediated by a reduction in pulmonary vascular remodelling. Targeting OPG with a therapeutic antibody is a potential treatment strategy in PAH. Pulmonary arterial hypertension (PAH) is characterised by progressive pulmonary vascular remodelling. Here, Arnold et al. develop a therapeutic antibody targeting osteoprotegerin and find it attenuates pulmonary vascular remodelling in multiple rodent models of PAH, alone or in combination with standard of care vasodilator therapy.